Qualitative Analysis of Cognitive and Affective Aspects of the Implementation of STEM Workshops in Early Childhood Classrooms (Revista Lusófona de Educação, 2026)
Early childhood is a critical period for fostering scientific thinking. However, approaches typically employed in early years classrooms often prioritise play over didactic aims, and there are few initiatives specifically targeting scientific learning. This study aimed to design and implement an inquiry-led experimental workshop project focused on mixtures and analyse its cognitive and emotional impact on preschool children. The intervention involved 35 four-year-old pupils from two educational institutions. Data were collected through structured interviews conducted before and during the intervention. Drawings produced by the participants at the end of the workshops also provided insight into their level of knowledge at the conclusion of the process. The pupils' emotions were also assessed via a satisfaction questionnaire. Data analysis revealed that initially, the children did not make predictions that were aligned with scientific concepts. However, by the end of the workshops, they had developed a preliminary conceptual model concerning mixtures, solubility and flotation. The results also demonstrate growing interest among the pupils in scientific learning and engaging with experimental activities.